Clinical Outcomes and Device-Related Complications Following Flow Diverter Stent Treatment of Unruptured Intracranial Aneurysms: A Single-Center Retrospective Study - Necat Islamoglu; Ali Can Yalcin; Ilker Coven (Diagnostics, 2026)
Background/Objectives: Flow diverter stents are widely used for the treatment of complex, unruptured intracranial aneurysms. Nitinol-based devices offer improved flexibility and vessel conformability; however, real-world clinical outcome data remain limited. This study aimed to evaluate the safety and clinical outcomes of nitinol-based flow diverter stents in a single-center cohort. We hypothesized that these devices would demonstrate high technical success rates, low rates of device-related complications, and favorable functional outcomes at 6 months. Methods: We retrospectively analyzed 109 patients with unruptured saccular intracranial aneurysms treated with nitinol-based flow diverter stents between 2020 and 2025. Patients with ruptured aneurysms, non-nitinol devices, or incomplete 6-month follow-up data were excluded. Technical success, device-related complications, and clinical outcomes were assessed using standardized imaging follow-up at 1 month (CT angiography) and 6 months (digital subtraction angiography). Results: Technical success was achieved in 109/109 cases (100%). The internal carotid artery cavernous segment was the most common aneurysm location. Intra- and peri-procedural device-related complications occurred in 12/109 (11%) patients, all of which were successfully managed without permanent neurological deficit. During the 6-month follow-up, post-procedural device-related complications occurred in 5/109 patients (4.6%), all due to delayed stent thrombosis requiring mechanical thrombectomy. One patient died due to persistent stent occlusion, and one patient developed unilateral lower-extremity plegia. Three patients experienced transient, non-device-related hypoesthesia that resolved during follow-up. At 6 months, most patients had favorable functional outcomes, with modified Rankin Scale scores of 0–1. Complete aneurysm occlusion was achieved in 83 of 108 patients (76.9%) at the 6-month angiographic follow-up. Conclusions: Flow diverter stents demonstrated high technical success and favorable clinical outcomes. Fishmouth deformity emerged as a potentially important technical factor associated with thrombotic complications and warrants careful recognition during deployment and follow-up.